Freedom of Religion amid Polarization and Religious Moderation Policy - Cholil, Suhadi (Interreligious studies and intercultural theology, 2022)
To address religious extremism and radicalism, the Indonesian government initiated the idea of "religious moderation" as an official state policy centered at the Ministry of Religious Affairs. Since 2019 the government has published books, guidance, and held various trainings on religious moderation, especially in institutions related to the Ministry. It also develops religious moderation instruments to ensure that government employees and officials, especially those within the Ministry, are free from exposure to extremism and radicalism. The idea is presented by the government as appreciating, respecting, and protecting the valued religious pluralism in Indonesia. But this article also argues that, upon critical examination, there are tensions between this idea and freedom of religion or belief in Indonesia. The religious moderation policy may run counter to freedom of religion or expression and overlooks central weaknesses in the existing state governance of religion.